2021
DOI: 10.18203/2320-1770.ijrcog20211143
|View full text |Cite
|
Sign up to set email alerts
|

Tocolytic effect of combined sildenafil citrate and nifedepine versus nifedipine alone for management of preterm labour at a tertiary centre

Abstract: Background: This study was conducted to evaluate tocolytic effect of sildenafil citrate and nifedipine versus nifedipine alone for management of preterm labour.Methods: Prospective randomized study on 80 women aged 18-35 years with singleton pregnancy of 28-34 weeks gestation with preterm labour, fulfilling the inclusion criteria were randomly divided in two groups of 40 each. In regimen A women were given sildenafil citrate and nifedipine while in regimen B nifedipine alone for 72 hours as tocolysis.Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
0
0
Order By: Relevance
“…In this study, majority of the participants in groups A and B belonged to primigravida with 86.67% and 73.33%, respectively. Urmila Karya et al 12 conducted a prospective randomized study on 80 women in which majority of the participants in the nifedipine and combination group belonged to multigravida with 65% and 62.5%, respectively, which was contradictory to our study.…”
Section: Discussioncontrasting
confidence: 95%
See 3 more Smart Citations
“…In this study, majority of the participants in groups A and B belonged to primigravida with 86.67% and 73.33%, respectively. Urmila Karya et al 12 conducted a prospective randomized study on 80 women in which majority of the participants in the nifedipine and combination group belonged to multigravida with 65% and 62.5%, respectively, which was contradictory to our study.…”
Section: Discussioncontrasting
confidence: 95%
“…Maternal side effects in group A were tachycardia, palpitations, nausea, and vomiting with 26.67%, 3.33%, and 16.67%, while in group B, tachycardia, facial flushing, palpitations, and headache were identified with 10%, 6.67%, 10%, 6.67%. In Urmila Karya et al 12 study, facial flushing, palpitations, headache, and nausea were the side effects identified within the nifedipine group with 22.5%, 10%, 25%, and 7.5%, and was 42.5%, 7.5%, 40%, and 5% respectively which resembles our study.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations